The Implementation of an Arabic Language Environment to Enhance Kalam Skills of Science Stream Students in a Boarding School - Nadiah Hutami Ningrum; Muslimin; Sri Wahyuningsih (Jurnal Penelitian Pendidikan IPA, 2025)
This research aims to examine the implementation of the Arabic language environment to enhace kalam skills of science stream students in a boarding school. The method used by the researcher in this study is qualitative research. This research is categorized as field research, where data is obtained directly from the research location, namely the science class at Boarding School MAN 2 Bima City. Data collection was conducted through observation and interviews. The researcher studied the application of the Arabic language environment directly by involving students, teachers, and the school as research subjects. As a result of the research conducted, it can be concluded that the application of the Arabic language environment at Boarding School MAN 2 Bima City plays an important role in improving students' speaking skills. Various programs implemented, such as mufrodat memorization, muhadatsah, tausiah, Arabic Week, and yellow book learning, provide an intensive communication experience for students. Periodic evaluations and coaching for new students also support the successful implementation of this language environment. From the results of the research, it can be seen that students are more accustomed, confident, and able to use Arabic in their daily lives.